Local anaesthetics combined with vasoconstrictors in patients with cardiovascular disease undergoing dental procedures: systematic review and meta-analysis protocol - Guimaraes, Caio Chaves; Lopes Motta, Rogerio Heladio; Bergamaschi, Cristiane de Cassia; Araujo, Jimmy de Oliveira; Andrade, Natalia Karol de; Figueiro, Mabel Fernandes; Ramacciato, Juliana Cama; Lopes, Luciane Cruz [UNESP] (Bmj Publishing Group, 2017)
Introduction The use of vasoconstrictors combined with local anaesthetics (LAs) in dentistry for patients with cardiovascular disease (CVD) is still controversial in the scientific literature. It raises concerns regarding the possibility of transient episodes, triggering negative cardiovascular outcomes. Method/design Trials eligible for our systematic review will enrol patients with CVD who have undergone dental treatments carried out with the use of LAs by comparing two arms: LAs with vasoconstrictors and LAs without vasoconstrictors. The research will be conducted in the electronic databases, namely Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, Healthstar (via Ovid), Cumulative Index to Nursing and Allied Health Literature and Web of Science, from their inception to December 2017, without any restrictions in terms of language and status of publication. A team of reviewers will independently assess titles, abstracts and complete text to determine eligibility. For eligible studies, the same reviewers will perform data extraction and evaluate the risk of bias in the selected articles. The selected outcomes comprise death, mortality by a specific cause, stroke, acute myocardial infarction, hospitalisation, pain, bleeding, arrhythmias, ischaemic episodes, anxiety, adverse effects, changes in blood pressure, changes in heart rate, anxiety and results obtained via oximetry. Whenever possible, we will conduct a meta-analysis to establish the effects of LAs with and without vasoconstrictors in the patients with CVD, and the overall quality of evidence for each outcome will be determined using the Grading of Recommendations Assessment, Development and Evaluation classification system. Ethics and dissemination Ethics committee approval was not necessary because this is a protocol of systematic review. This systematic review will be submitted for presentation at conferences and for publication in a peer-reviewed journal. Our review will assess the risks of cardiovascular events when using LAs with and without vasoconstrictors in patients with CVD, focusing on important clinical outcomes.